MUNICIPALITIES' INVESTMENT PROSPECTS ASSESSMENT - D. V. Ivanov; A. S. Sokolitsyn (Дискурс, 2018)
The paper reviews basic methodological approaches to assessing municipalities investment prospects, analyzing advantages and disadvantages of existing approaches. A group of methods most fully reflecting municipalities specifics compared to other investment facilities is selected. It is shown that the best way to present consolidated data assessing municipality investment prospects is compiling its investment project profile. A model form for investment project profile is suggested to increase potential investors' awareness.